Florida Cow-Calf and Stocker Beef Safety and Quality Assurance Handbook: Introduction - Todd A. Thrift; Matt J. Hersom; Max Irsik (EDIS, 2006)
AN170, is the first 14 pages of the Florida Cow-Calf and Stocker Beef Safety and Quality Assurance Handbook, which is used for the voluntary Florida Beef Quality Producer program. It introduces the concepts of Beef Quality Assurance (BQA), Total Quality Management (TQM) and the Hazard Analysis Critical Control Point system (HACCP) to Florida beef producers and describes the objectives of the program, providing many reasons for producers to participate. Produced as part of a cooperative program by Florida Cattlemen's Association, Florida Department of Agriculture and Consumer Services, and the University of Florida (IFAS) Extension Service. Published by the UF Department of Animal Sciences, October 2006.